Mayo clinic book of alternative medicine - Bauer, Brent (Time Inc. Home Entertainment Books, 2010)
An overview of complementary and alternative medicine discusses various treatments, including herbs and energy therapies, and examines how alternative and conventional therapies can be combined to treat twenty common conditions.